Oral Vaccination Approaches for Anti-SHIV Immunity - Velarde de la Cruz, Erandi; Wang, Lingyun; Bose, Deepanwita; Gangadhara, Sailaja; Wilson, Robert L.; Amara, Rama R.; Kozlowski, Pamela A.; Aldovini, Anna (Frontiers in Immunology, 2021)
We modified a Sabin Oral Poliovirus Vaccine (OPV) vector to permit secretion of the antigens of interest with the goal of improving anti-HIV Env humoral responses in a SHIV mucosal immunization composed of DNA and recombinant OPVs. We evaluated stimulation of systemic and mucosal cell-mediated and humoral immunity in Rhesus macaques by two regimens, both involving a prime with a SHIVBG505 DNA construct producing non-infectious particles formulated in lipid nanoparticles, administered in the oral cavity, and two different viral vector boostings, administered in the oral cavity and intestinally. Group 1 was boosted with rMVA-SHIVBG505, expressing SIV Gag/Pol and HIVBG505 Env. Group 2 was boosted with a SHIVBG505-OPV vaccine including a non-secreting SIVmac239CA-p6-OPV, expressing Gag CA, NC and p6 proteins, and a HIVBG505C1-V2-OPV, secreting the C1-V2 fragment of HIV EnvBG505, recognized by the broadly neutralizing antibody PG16. A time course analysis of anti-SHIV Gag and Env CD4+ and CD8+ T-cell responses in PBMC and in lymph node, rectal, and vaginal MNC was carried out. Both regimens stimulated significant cell-mediated responses in all compartments, with SHIVBG505-OPV immunization stimulating more significant levels of responses than rMVA- SHIVBG505. Boolean analysis of these responses revealed predominantly monofunctional responses with multifunctional responses also present in all tissues. Stimulation of antibody responses was disappointing in both groups with negative anti-SHIV IgG in plasma, and IgA in saliva, rectal and vaginal secretions being restricted to a few animals. After repeated rectal challenge with SHIVBG505, two Group 1 animals remained uninfected at challenge termination. No significant differences were observed in post-infection viral loads between groups. After the acute phase decline, CD4+ T cell percentages returned to normal levels in vaccinated as well as control animals. However, when compared to controls, vaccinate groups had more significant preservation of PBMC and rectal MNC Th17/Treg ratios, considered the strongest surrogate marker of progression to AIDS. We conclude that the vaccine platforms used in this study are insufficient to stimulate significant humoral immunity at the tested doses and schedule but sufficient to stimulate significant mucosal and systemic cell-mediated immunity, impacting the preservation of key Th17 CD4+ T cells in blood and rectal mucosa.